Makna Metafungsional dalam Novel Penyelamat Kakakku Karya Jodi Picoult - Yin, Roni Lo Vun; Maman, Mayong (JENTERA: Jurnal Kajian Sastra, 2025)
This study aims to analyze the realization of metafunctional meaning (textual, interpersonal, ideational) and ideology in the novel Penyelamat Kakakku by Jodi Picoult with a functional systemic linguistic approach, descriptive qualitative method. Data collection through documentation, reading, and note-taking techniques that are analyzed by triangulation. The analysis reveals the author's ideology that emphasizes individual rights, family authority, and the relativity of meaning that textually, ideationally, and interpersonally criticizes the power structure and restrictive social norms, while fighting for bodily autonomy and individual freedom. The research findings correlate with the development of critical literacy, literature based on human values, and character development that emphasizes social sensitivity and critical thinking skills towards social reality. Abstrak Penelitian ini bertujuan menganalisis realisasi makna metafungsional (tekstual, interpersonal, ideasional) dan ideologi dalam novel Penyelamat Kakakku karya Jodi Picoult dengan pendekatan linguistik sistemik fungsional, metode kualitatif deskriptif. Pengumpulan data melalui teknik dokumentasi, baca, dan catat yang dianalisis secara triangulasi. Analisis mengungkap ideologi penulis yang menekankan hak individu, otoritas keluarga, dan relativitas makna yang secara tekstual, ideasional, dan interpersonal mengkritik struktur kuasa serta norma sosial yang mengekang, sekaligus memperjuangkan otonomi tubuh dan kebebasan individu. Temuan penelitian berkorelasi dalam pengembangan literasi kritis, sastra berbasis nilai kemanusiaan, serta pengembangan karakter yang menitikberatkan pada kepekaan sosial dan kemampuan berpikir kritis terhadap realitas sosial.